The Relationship Between Political Volunteers of the Dozer Team and Voters in Shaping Political Participation in the 2024 South Sulawesi Regional Elections - Rully Rozano; Armin Arsyad; Gustiana A. Kambo (Universitas Wahid Hasyim Semarang, 2026)
This study aims to analyze how relationships between non-party political volunteers and voters shape political participation in the 2024 South Sulawesi local election. The research employs a qualitative approach with an intrinsic case study design, utilizing in-depth interviews, participant observation, and documentation as data collection methods. The subjects of the study include Dozer political volunteers and voters in Makassar City, Gowa Regency, and Maros Regency. Data were analyzed using layered thematic analysis. The findings reveal that voter participation is formed through multilayered social relationships consisting of interpersonal, emotional, and instrumental relations. Interpersonal relations build trust and social legitimacy, emotional relations strengthen political attachment and loyalty, while instrumental relations translate these attachments into concrete electoral actions. This study highlights that local political participation should be understood as a socially embedded practice and underscores the strategic role of non-party political volunteers in local political mobilization. Keywords: Non-party political volunteers; political participation; social relations; local elections; local democracy.